PENGEMBANGAN METODE DEMONSTRASI DALAM PEMBELAJARAN BIOLOGI DI SMK KESEHATAN SAMARINDA (KEANEKARAGAMAN HAYATI) - Afdal Afdal (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This study aims to develop a demonstration method in learning biology on the subject of biodiversity at SMK Kesehatan Samarinda. This study is a qualitative research . The research subjects were students of class XI. In this case, the researcher did not act as an executor of action research. The data were collected through observation and interviews. The data of student learning outcomes were obtained through tests and then they were analyzed up to getting the conclusion. The data analysis were used to obtain: (1) the implementation of learning through development of demonstration method application, (2) development of accurate demonstration methods (3) student learning outcomes through the implementation of demonstration method development. The research results showed that: (1) The implementation of demonstration method development can help teachers to manage the classroom and to develop a method of learning itself, so that it becomes fun and teaching materials are more easily understood by the student, (2) The implementation of demonstration method development is able to improve students’ learning outcomes which were indicated with an improvement in the number of students who experience learning comprehensivess of the implementation of the new demonstration method development phase I and phase II, (3) the development of demonstration methods is more effective if it is conducted outside the classroom. Thus, the implementation of demonstration method development is effective to improve student learning outcomes.